1997
DOI: 10.3109/00016349709024592
|View full text |Cite
|
Sign up to set email alerts
|

Can women with intrapartum rupture of anal sphincter still suffer after‐effects two decades later?

Abstract: Women with intrapartum anal sphincter rupture can still suffer problems 20 years afterwards. In the follow-up of these women, information and support are essential and active tracing of such women is to be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
26
1
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 4 publications
15
26
1
3
Order By: Relevance
“…Earlier studies have shown that persistent sphincter damage occurs in up to 88% 4–6 and anorectal complaints in up to 50% 5–8 . Only three studies with follow up of more than 15 years comparing faecal incontinence in women with and without anal sphincter damage have been published and have shown contradictory results 8–10 . Nygaard et al found no significant difference between 29 women with obstetric sphincter rupture, 89 women with a midline episiotomy and 33 women delivered by caesarean section, whereas Haadem and Gudmondson described an increased risk of incontinence in 41 women with obstetric sphincter rupture compared with 38 controls.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that persistent sphincter damage occurs in up to 88% 4–6 and anorectal complaints in up to 50% 5–8 . Only three studies with follow up of more than 15 years comparing faecal incontinence in women with and without anal sphincter damage have been published and have shown contradictory results 8–10 . Nygaard et al found no significant difference between 29 women with obstetric sphincter rupture, 89 women with a midline episiotomy and 33 women delivered by caesarean section, whereas Haadem and Gudmondson described an increased risk of incontinence in 41 women with obstetric sphincter rupture compared with 38 controls.…”
Section: Introductionmentioning
confidence: 99%
“…Data based on patients' memories are often inaccurate. When questioned 20 years after delivery in a retrospective case-control study, 12% of the women with anal sphincter rupture were unaware that they had sustained such a rupture, and 5% of the controls imagined that they had sustained a rupture [16]. Indeed, the association between the memory of an important perineal tear or a long delivery and subsequent anal incontinence could be related not only to anal sphincter rupture but to another dysfunction in the continence mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Il existe également une association entre périnée complet et dyspareunie [29,30]. À long terme (15 ans et plus), le risque d'incontinence anale ou de dyspareunie est controversé, certaines études cas-témoins retrouvent un risque accru [30,64], tandis que d'autres ne retrouvent plus de lien [65,66].…”
Section: Périnée Complet Et Déchirures Occultesunclassified